Ecological Justice: Optimizing Financing for the Transition to New and Renewable Energy Through Green Financing - Dwi Elok Indriastuti; Nur Hidayatul Fithri; Farina Gandryani (Mimbar Keadilan, 2025)
The transition to renewable energy became a current issue following the drafting of the New and Renewable Energy Bill. One problem with this transition is related to funding, which requires large funds, making it not possible to depend on funds derived from the state budget. Therefore, this article will analyze the optimization of funding from the private sector through green financing schemes. This is normative research through statute, conceptual and comparative approaches. The results show that reflecting on the implementation of green financing in China and South Africa, the formulation of Articles in the Draft Bill on Renewable Energy should explicitly mention green financing instruments such as green bonds and green sukuk as one of the sources of funding for the transition. The Draft Bill must also involve elements from the Financial Services Authority in its technical implementation. Moreover, the Financial Services Authority has issued POJK Number 18 of 2023 which can be linked to other funding sources for the transition to renewable energy.